Effects of exogenous enzymes on nutrient digestibility, ruminal fermentation and growth performance in beef steers - Salem, A. Z. M. (2013)
Forty crossbred steers (Baladi×Friesian, average BW 153±5.14kg) were used to evaluate the effects of exogenous enzyme (ENZ) addition on nutrient intake, digestion, ruminal fermentation and feed conversion in beef steers. Steers were randomly assigned to two groups of 20 animals and fed individually a total mixed ration (TMR) without (CTRL) or with addition of 40g/hd/d of an enzyme mixture (ZADO®). The ENZ mixture was added for 220 days and in vivo apparent digestibility was measured on days 210-220. Enzyme addition did not affect (P=0.1) DM intake, whereas it increased (P<0.05) total tract apparent digestibility of all nutrients. The magnitude of improvement in digestibility varied among nutrients, with the highest improvement occurring in digestibility of NDF and ADF (21.8% and 26.7%, respectively). Addition of ENZ also increased (P<0.05) concentrations of rumen ammonia N and total short chain fatty acids (SCFA) before and 3h post-feeding. Allantoin concentration total purine derivates were increased (P=0.04) with enzyme addition while uric acid was not affected (P=0.05). Live-weight gain was also higher (P<0.01) in steers supplemented with ENZ. In conclusion, adding the exogenous enzyme product increased live-weight gain by 16% due to increased nutrient digestibility.